A review of leadership theories: identifying a lack of growth in the HRD leadership domain. Issue 7 (19th October 2018) - Turner, John R.; Baker, Rose
Abstract : Purpose: This paper aims to identify the life-cycle of leadership theory from both the human resource development (HRD) and the organizational/leadership literature while providing a contrast between the two bodies of literature. The current research identifies which theories are being represented within the HRD literature, followed by a review of current directions in the leadership fields, primarily from literature in the organizational and leadership fields. By identifying these two bodies of leadership theories, the following research question will be answered: How current are the leadership theories provided in the literature of HRD compared to research that is reported from other external leadership fields? Design/methodology/approach: This paper examines how leadership theories are represented in the HRD literature. Data for the current article provide a preview of leadership theories that are used to inform HRD scholars and scholar–practitioners for a period of 15 years (2000-2015) in the four Academy of Human Resource Development (AHRD) publications (Advances in Developing Human Resources; Human Resource Development International; Human Resource Development Quarterly; and Human Resource Development Review). The four journals within the AHRD were reviewed to identify which leadership theories were being researched and used to inform members of HRD. The search terms for the current study included "leadership AND theory, " "team AND leadership, " "leadership AND development" and "team AND development." Studies that presented a leadership theory and either described or defined the theory were coded for the current study. Within this body of literature, there were a total of 74 leadership theories identified (some repeating), among those there were a total of 20 unique leadership theories. The literature external of HRD was identified using the ScienceDirect database for 10 years (2007-2017) with the topics limited to "topics–leadership." Once the HRD and organizational/leadership literature are presented, a comparison between the two literature streams will be provided, highlighting any deficiencies within either body of literature and recommendations for future research efforts for the field of HRD. Findings: This examination of leadership theory study within HRD and other fields highlights the deficiencies within either body of literature and offers recommendations for future research efforts for the field of HRD. In line with the trend in leadership research, HRD should call for more longitudinal and multi-level research efforts to be conducted as opposed to cross-sectional studies. Research limitations/implications: The current study is limited in the literature that was used to collect/code data. Also, the time frame for the HRD literature ended in 2015 due to the long duration required to review articles and to code the data. Secondary data were obtained from organizational/leadership literature and are more current because they are more recent. Overall, even with an end date of 2015 for the HRD literature, the HRD field has not changed too much during this time and the authors recognize some minor changes, but the research findings are still relevant and the leadership deficits presented are still realized. Practical implications: The field of HRD is behind when it comes to leadership theories. This paper identifies this in an effort to aid researchers, students and practitioners to look beyond the leadership theories presented in the HRD literature for more relevant and current leadership theories. This paper highlighted a number of newer and current leadership theories and trends for scholars and scholar-practitioners to begin to focus on; however, this list is only a snapshot and is bounded by the data collected for the current paper. Originality/value: This paper is original in that it is both critical of leadership research within the HRD literature while also providing new directions for the field. The snapshot of where the field of HRD is compared to the leadership and organizational fields becomes apparent with multiple future directions for research.